Seguridad informática mediante hacking ético en la aplicación de pentesting para el análisis de vulnerabilidades en las redes de datos de la cooperativa SIERRA CENTRO sucursal La Maná, provincia de Cotopaxi. - Garcia Vega, Ana Rebeca (2022)
The Sierra Centro Savings and Credit Cooperative is a financial institution in the province of Cotopaxi which provides financing services and fundraising, operations and financial services providing confidence and security to promote the local social and economic development of its customers. Taking into account and given the importance of the information manipulated by the financial departments of private entities, it is necessary to implement mechanisms that support computer security that protect data and information both from shared resources and the interaction of a data network, thus allowing to placate the resources that may be exposed to their security breaches being violated through access to certain information. This research is based on the application of pentesting through ethical hacking in data networks under the ISO 27001 (International Organization for Standardization) standard applied in the Sierra Centro Savings and Credit Cooperative, La Maná branch, which will allow the information to be secure and free of computer attacks through the application of technical analysis in the detection of vulnerable gaps; implementing security rules by using Kali Linux as an offensive security operating system that allows a secure and correct administration, by monitoring the data networks of the private entity.